Development of Fe/SiBr/Si₃N₄/silica fume nanocomposites from recycled metal waste for industrial applications - Mohammed A. Taha; S. A. Gad; Rasha A. Youness (Scientific Reports)
Abstract Due to the high cost of raw materials, this work aims to benefit from metal waste, especially iron (Fe) and silicon bronze, which results from turning workshops and recycling them to obtain nanocomposites for industrial applications. In this respect, Fe/SiBr/Si3N4/silica fume nanocomposites possessing superior mechanical, wear, and magnetic characteristics have been produced using powder metallurgy (PM) technology. Milled sample particle size, crystal size, and phase composition were investigated using X-ray diffraction (XRD) technique and transmission electron microscopy (TEM). The powders were compressed and sintered in argon to get excellent sinterability. The sintered nanocomposites’ physical, mechanical, wear, electrical, and magnetic properties were investigated. The microstructure was also examined using field emission scanning electron microscopy (FESEM). The results showed a noticeable decrease in the size of particles and crystallite size after adding reinforcements, reaching 22 nm for the sample improved with 5 vol% silica fume and 5 vol% Si3N4 (FS4). In addition, after adding reinforcements, there was a clear improvement in the microhardness, Young’s modulus, and wear rate of Fe-SiBr, reaching 58, 27.89, and 43.21% percent for the sample FS4. Adding reinforcements harms the electrical conductivity of Fe-SiBr, as it decreases to 8.64 × 106 S/m for the same previous sample. Finally, adding reinforcements slightly affects the decrease in magnetization of the nanocomposites.